Metabolism and growth inhibitory activity of cranberry derived flavonoids in bladder cancer cells. Issue 9 (26th August 2016) - Prasain, Jeevan K.; Rajbhandari, Rajani; Keeton, Adam B.; Piazza, Gary A.; Barnes, Stephen
Abstract : In the present study, anti-proliferative activities of cranberry derived flavonoids and some of their in vivo metabolites were evaluated using a panel of human bladder tumor cell lines (RT4, SCABER, and SW-780) and non-tumorigenic immortalized human uroepithelial cells (SV-HUC). Abstract : In the present study, anti-proliferative activities of cranberry derived flavonoids and some of their in vivo metabolites were evaluated using a panel of human bladder tumor cell lines (RT4, SCABER, and SW-780) and non-tumorigenic immortalized human uroepithelial cells (SV-HUC). Among the compounds tested, quercetin 3- O -glucoside, isorhamnetin (3′- O -methylquercetin), myricetin and quercetin showed strong concentration-dependent cell growth inhibitory activities in bladder cancer cells with IC50 values in a range of 8–92 μM. Furthermore, isorhamnetin and myricetin had very low inhibitory activity against SV-HUC even at very high concentrations (>200 μM) compared to bladder cancer cells, indicating that their cytotoxicity is selective for cancer cells. To determine whether the differential cell growth inhibitory effects of isomeric flavonoids quercetin 3- O -glucoside (active) and hyperoside (quercetin 3- O -galactoside) (inactive) are related to their metabolism by the cancer cells, SW-780 cells were incubated with these compounds and their metabolism was examined by LC-MS/MS. Compared to quercetin 3- O -glucoside, hyperoside undergoes relatively less metabolic biotransformation (methylation, glucuronidation and quinone formation). These data suggest that isorhamnetin and quercetin 3- O -glucoside may be the active forms of quercetin in prevention of bladder cancer in vivo and emphasize the importance of metabolism for the prevention of bladder cancer by diets rich in cranberries.